Um Modelo de distribuição de renda e inflação por conflito entre salários, lucro e renda de monopólio de serviços monitorados - Haluska, Guilherme; Summa, Ricardo; Maccari Lara, Fernando (Brazilian Keynesian Review, 2023)
In the present paper we present a model of inflation and functional income distribution following the cost-push and distributive conflict approach. Our specific contribution is to consider in an integrated approach the effects of the bargain over money wages, the monetary policy and the government policy for monitored prices over inflation and functional income distribution, admitting the existence of monopoly profits in the sector that produces the monitored good and the possibility that the rates of profits might not be homogeneous between the sectors producing the monitored goods and the other  sectors. We conclude that it is necessary to take into consideration that the set of mentioned policies influences not only inflation, but also the functional distribution of income. Also, we see that some determined inflation rate can be achieved with several different distributive outcomes, depending on the set of policies adopted.